The French colonial occupation and the Algerian National Identity: alienation or assimilation - Ladjal, Tarek; Bensaid, Benaouda (Inder-sciences, 2012)
The problem of cultural identity continues to plague the Algerian society half a century after liberation from French colonisation in 1962. This paper seeks to analyse the question of Algerian national identity during the French colonial occupation, discuss its causes, manifestations and ramifications, and examine the policies of alienation and assimilation adopted by the French authorities in their treatment of their subjects. This study shows that issues of culture and identity were continually used as strategies of control and domination, and that both of these policies carried out decisive impact on both the past and present development of Algeria.